1997
DOI: 10.1002/(sici)1097-0347(199705)19:3<205::aid-hed7>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Depth of invasion as a predictive factor for cervical lymph node metastasis in tongue carcinoma

Abstract: Background Many histopathologic parameters in head and neck squamous cell carcinoma have been identified as predictive factors for cervical metastasis. Several studies focused on tumor thickness, and the depth of invasion was suggested to have a relationship to the occurrence of cervical metastasis. Nonetheless, the criterium for elective neck therapy in terms of tumor depth is still inconclusive. Therefore, a retrospective study was undertaken to substantiate the differing results in the literature with our o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
190
4
10

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 314 publications
(211 citation statements)
references
References 13 publications
7
190
4
10
Order By: Relevance
“…Histopathologic factors like tumor thickness, perineural and microvascular invasions, lymphocytic inflammatory infiltration, pattern of tumor invasion and differentiation, and molecular tumor markers have been advocated to be reliable metastastic potential parameters [45,58,97,150,166]. A report on a multivariable clinicopathologic scoring system in which points were allotted to each individual variable or predictor has been document [135].…”
Section: Diagnosing the Node-negative Neckmentioning
confidence: 99%
See 2 more Smart Citations
“…Histopathologic factors like tumor thickness, perineural and microvascular invasions, lymphocytic inflammatory infiltration, pattern of tumor invasion and differentiation, and molecular tumor markers have been advocated to be reliable metastastic potential parameters [45,58,97,150,166]. A report on a multivariable clinicopathologic scoring system in which points were allotted to each individual variable or predictor has been document [135].…”
Section: Diagnosing the Node-negative Neckmentioning
confidence: 99%
“…Neck node status is the single most important prognostic factor in oral cancers and other head and neck cancers [26]. The incidence of lymph node metastases of these cancers depends largely on histo-pathologic factors like tumor thickness, perineural and microvascular invasions, lymphocytic inflammatory infiltration, pattern of tumor invasion and differentiation, and molecular tumor markers [45,58,140,150].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be due to the inclusion of more T2 patients (66%) as compared to Yuen's randomized trial (39%). Fukano [4] studied 34 patients with tongue SCC, all stages, but separated out the data for cN0 patients . No occult metastases were associated with depth of invasion \3 mm.…”
Section: Predictors Of Occult Metastases: Tumor Depth Of Invasionmentioning
confidence: 99%
“…Many studies subsequently have shown a strong correlation between the thickness of tumor and lymph node metastasis. Using <3 mm as a cutoff value Yuen et al [22,23].…”
Section: Discussionmentioning
confidence: 99%